Enfermedad arterial periférica en pacientes diabéticos tipo 2, del grupo Mi enfermedad a la raya Centro de Salud N° 3 Loja - Agudelo Contecha, Inukapula Kapppujadar (2021)
Type 2 diabetes mellitus (DM2) is a systemic disease whose complications include peripheral arterial disease (PAD). This disease is characterized by accumulation of atheromatous plaques in the arterioles; PAD is much more aggressive in diabetics, with a 1% increase in HbA1c it produces a 25% increase in the risk of PAD, for which the ankle-brachial index is a useful tool to determine the involvement of the lower limbs and the cardiovascular damage. The present study aimed to determine the prevalence of PAD in patients with T2DM, risk factors that intervene in PAD and their relationship with the evolution of T2DM. The study had a quantitative, descriptive, prospective, cross-sectional approach. Using 100% of the sample, 91 members of the group "My Illness a la Raya" of the Health Center N ° 3 in Loja, who answered a survey where specific data were obtained. The prevalence of PAD was established with 18% by ABI and 63%, by the Edinburgh questionnaire, it also appeared in people over 65 years with 31%, women stood out with 75%, arterial hypertension 68%, hyperlipidemia with 40%. We conclude that the prevalence of PAD is very narrow in patients with diabetes mellitus, between years 1 and 10 of diagnosis of DM2, establishing itself in the first decade of suffering from the disease, affecting women aged 66 years and over; being frequent the arterial hypertension and the hyperlipidemia Keywords: cardiovascular risk, arteriopathy, atherosclerosis, hyperglycemia